KAJIAN YURIDIS PENGADAAN TANAH BAGI KEPENTINGAN UMUM PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Cici Mindan Cahyani; Arief Rahman (Private Law, 2021)
This study describes how the land procurement for public interest works according to the Law No 11 of 2020 of Omnibus Law, as well as identifies the legal protection for landowners. This study is a normative one with statute, conceptual, and historical approach. Results of this study show that a number of articles’ revision in the Law thatare related to land procurement, simplify the process, those regarding strategic national projects in particular. Nonetheless, it is believed that the revision is highly likely to lead to environmental degradations and agrarian conflicts.